Cirrhotic cardiomyopathy: Appraisal of the original and revised criteria in predicting posttransplant cardiac outcomes. Issue 8 (16th June 2022) - Spann, Ashley; Coe, Christopher; Ajayi, Teminioluwa; Montgomery, Garren; Shwetar, Mohammed; Oje, Adesola; Annis, Jeffrey; Slaughter, James C.; Alexopoulos, Sophoclis; Brittain, Evan; Izzy, Manhal
Abstract: Cardiovascular disease (CVD) significantly contributes to morbidity and mortality after liver transplantation (LT). Cirrhotic cardiomyopathy (CCM) is a risk factor for CVD after transplant. CCM criteria were originally introduced in 2005 with a revision proposed in 2020 reflecting echocardiographic technology advancements. This study assesses the two criteria sets in predicting major adverse cardiac events (MACE) after transplant. This single‐center retrospective study reviewed adult LT recipients between January 1, 2009, and December 31, 2018. Patients with insufficient pre‐LT echocardiographic data, prior ischemic heart disease, portopulmonary hypertension, or longitudinal care elsewhere were excluded. The primary composite outcome was MACE (arrhythmia, heart failure, cardiac arrest, and/or cardiac death) after transplant. Of 1165 patients, 210 met the eligibility criteria. CCM was present in 162 patients (77%) per the original criteria and 64 patients (30%) per the revised criteria. There were 44 MACE and 31 deaths in the study period. Of the deaths, 38.7% occurred secondary to CVD. CCM defined by the original criteria was not associated with MACE after LT ( p  = 0.21), but the revised definition was significantly associated with MACE (hazard ratio [HR], 1.93; 95% confidence interval, 1.05–3.56; p  = 0.04) on multivariable analysis. Echocardiographic variable analysis demonstrated low septal e' as the most predictive variable for MACE after LT (HR, 3.45; p  < 0.001). CCM, only when defined by the revised criteria, was associated with increased risk for MACE after LT, validating the recently revised CCM definition. Abnormal septal e', reflecting impaired relaxation, appears to be the most predictive echocardiographic criterion for MACE after LT.